Leviathan on a leash a theory of state responsibility - Fleming, Sean (Princeton University Press, 2020)
"The practice of holding states responsible is central to modern politics and international relations. States are commonly blamed, praised, punished, obligated, and held liable. On an almost-daily basis, one hears about the latest round of sanctions against the latest rogue state; about the latest treaty that states have signed or repudiated; about the latest heavily-indebted state that is on the brink of bankruptcy; or about what former colonial states owe to their former colonies. The assumption in each case is that the state-as distinct from its individual leaders, officials, or citizens-is the entity that bears the responsibility in question. This book examines the theoretical and normative underpinnings of state responsibility. Why, and under which conditions, should we assign responsibilities to whole states rather than to particular individuals? There are two prevailing theories of state responsibility. The first suggests that states can be held responsible because they are 'moral agents' like human beings, with similar capacities for deliberation and intentional action. A state is responsible in the same way in which an indivdiual is responsible. The second sthat states can be held responsible because they are legal persons that act vicariously through their officials; states are 'principals' rather than agents, and the model for state responsibility is a case of vicariously liability, such as when an employer is held financially liable for the actions of her employee. Sam Fleming reconstructs and develops a forgotten understanding of state responsibility from Thomas Hobbes' political thought. Like proponents of the two theories of state responsibility, Hobbes considered states to be 'persons', meaning that actions, rights, and responsibilities can be attributed to them. States can be said to wage war, possess sovereignty, and owe money. What makes Hobbes unique is that he does not consider states to be agents or principals. Unlike an agent, the state cannot will or act on its own; it needs representatives to will and act on its behalf. Unlike a principal, the state cannot authorize its own representatives. States are in some ways similar to "Children, Fooles, and Mad-men that have no use of Reason", who are "Personated by Guardians, or Curators; but can be no Authors" Although the state is incapable of acting on its own, it can nevertheless exercise rights and incur responsibilities through the representatives that its subjects authorize to act in its name. Hobbes' "Artificiall Man" is conceptually more like an artificial child or "Foole""--